Skandinaviskt mottagande och användande av Montesquieus maktdelningslära - En analys av Montesquieus maktdelningslära och hur den användes i de skandinaviska författningarna introducerade mellan 1809 och 1849 - Vlachos,Elias (2025)
During the first half of the nineteenth century new constitutions were adopted in all Scandinavian countries. Sweden introduced the 1809 Instrument of Government, followed by the Norwegian Constitution of 1814 and the Dan-ish Constitution of 1849. These constitutional reforms took place during a time of significant development in constitutional theory. One of the theorists who contributed to these innovations was Charles Louis de Secondat Mon-tesquieu with his work The Spirit of Laws from 1748. One of Montesquieu’s lasting contributions was the doctrine of the separation of powers, which be-came a central constitutional principle. The aim of this essay is to analyse how, and to what extent, the Scandinavian constitutions interpreted and im-plemented Montesquieu’s theory, as well as to identify similarities and differ-ences in their approaches. The essay finds that Montesquieu’s overarching objective was the creation of political liberty. This objective was achieved by creating a constitution which balanced not only between the legislative, executive and judicial branches of government, but also between different social groups. Montesquieu identified three main social groups, the monarch, the nobility and the people, and em-phasised the risk that any one of them could dominate the others through the control of governmental institutions. To mitigate this risk the constitution needed a functional separation of powers, preventing institutions from exer-cising authority across branches. It also required a personal separation, pro-hibiting individuals from simultaneously holding offices in multiple branches. In addition, the branches had to exercise mutual control through a system of checks and balances. The analysis demonstrates that the Scandinavian constitutions incorporated Montesquieu’s ideas to a varying degree. The Norwegian Constitution of 1814 separated the branches of government in a manner akin to Montes-quieu’s model but did not share his objective of balancing power between social groups. As a result, the Storting was granted a degree of legislative dominance exceeding what Montesquieu considered ideal. By contrast, the Swedish Instrument of Government of 1809 shared Montes-quieu’s overarching objectives. The estate-based Riksdag, intended to repre-sent different segments of society, together with advanced mechanisms of constitutional control were in line with key elements of Montesquieu’s theory. However, the king was given extensive powers with control over two of the governmental branches and significant influence over the Riksdag. This con-flicted with Montesquieu’s stress on both institutional and personal separation of powers. The essay concludes that the Danish Constitution of 1849 is the closest equiv-alent to Montesquieu’s doctrine. Like the Swedish constitution it employed a representative assembly but divided into two chambers representing different social classes. Furthermore, it created a system where both the king and the chambers were able to exercise mutual checks and balances. Although the Danish constitution did not fully conform to Montesquieu’s model, for exam-ple through the existence of royal participation in the legislative process, it adhered to his overarching objective and most important principles. Overall, the essay finds that none of the Scandinavian constitutions fully im-plemented Montesquieu’s model. The Danish constitution of 1849 came the closest, while the Swedish and Norwegian ones diverged for distinct reasons.
Keywords: Rättshistoria; Legal history; Komparativ rätt; Comparative Law; Statsrätt